PERLINDUNGAN HUKUM PENGGUNA MEDIA SOSIAL INSTAGRAM YANG DIRUGIKAN PENGGUNAAN FAKE ACCOUNT - Aristayuni, Anak Agung Sagung; Dahana, Cokorda Dalem (Kertha Semaya : Journal Ilmu Hukum; Vol 11 No 4 (2023), 2023)
The purpose of this study was to analyze  reasons or backgrounds that Instagram users using fake accounts and the legal consequences of using fake accounts on Instagram. The research uses normative legal research with statutory and the conceptual approach. Data collected through library research and interviews on several teenagers in the neighborhood where the author lives. Based on the research, the majority of fake account users are looking for information freely by hiding their identity through fake accounts. Then, Article 35 of Law Number 11 of 2008 which was later amended by Law Number 19 of 2016 concerning Electronic Information and Transactions stipulates that anyone who intentionally manipulates or creates electronic information and/or electronic documents with the aim of pretending to be looks like authentic data. Based on this article, the legal consequence is a prison sentence of 12 (twelve) years and/or a maximum fine of twelve billion rupiah, based on Article 51 of Law Number 11 of 2008.